Metabolic Footprint Analysis of Volatile Organic Compounds by Gas Chromatography-Ion Mobility Spectrometry to Discriminate Mandarin Fish (Siniperca chuatsi) at Different Fermentation Stages - Wang, Yueqi; Wu, Yanyan; Shen, Yingying; Li, Chunsheng; Zhao, Yongqiang; Qi, Bo; Li, Laihao; Chen, Yufeng (Frontiers in Bioengineering and Biotechnology, 2021)
Chinese fermented mandarin fish (Siniperca chuatsi) have unique aroma characteristics that are appreciated by local consumers. In this study, electronic nose (E-nose) and gas chromatography–ion mobility spectrometry analysis were combined to establish a volatile fingerprint of fermented mandarin fish during fermentation. Clear separation of the data allowed mandarin fish samples at different fermentation stages to be distinguishing using E-nose analysis. Forty-three volatile organic compounds (VOCs) were identified during fermentation. Additionally, partial least squares discrimination analysis was performed to screen for different VOC metabolites in the fermented mandarin fish; the levels of six VOCs changed significantly during fermentation (variable importance in projection > 1; p < 0.05). Three VOCs, i.e., hexanal-D, nonanal, and limonene were identified as potential biomarkers for fermentation. This study provides insight into the flavor changes of traditional mandarin fish during fermentation and a theoretical basis for product quality control.